Peran Pemoderasi NPF dalam Pengaruh Financing Growth dan CAR terhadap Profitability H - Toyibah Masmuna, Hayatun; Yuliani, Yuliani; Muhammad Husni Thamrin, Kemas (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The aim of the study was to examine the effect of financing growth and Capital Adequacy Ratio (CAR) on profitability with Non Performing Financing (NPF) as moderation with a sample of 6 Islamic commercial banks registered with the Financial Services Authority during the 2011-2020 period. The analysis technique used is Moderated Regression Analysis (MRA). The results showed that financing growth had a positive and significant effect on profitability (ROA and ROE). CAR has a positive and significant effect on profitability (ROA), but not significant on profitability (ROE). In addition, the research results also show that NPF is not able to moderate the effect of financing growth on profitability (ROA and ROE). Conversely, NPF moderates by weakening the effect of CAR on profitability (ROA and ROE). In other words, profitability is expected to decrease because the use of bank capital is not optimal due to the large NPF value. This research contributes to Islamic commercial banks to carry out financing effectiveness and carry out CAR efficiency so that performance can improve financial performance.